OSCAR BERMÚDEZ MIRAL: RESEARCHER OF THE NORTE GRANDE, HISTORIAN OF THE NITRATE INDUSTRY, A MAN OF TWO WORLDS. - González Miranda, Sergio (Revista de Historia Social y de las Mentalidades, 2024)
The objective of this article is to do a  biographical sketch of the historian Óscar  Bermúdez, researcher of the Norte Grande  of Chile, especially of the nitrate period. To  reach the objective, they played his main  works, interviews and analyzed two previous  biographical studies about Bermúdez.  Nevertheless, the objective of this article is not  just to be a character’s biographical sketch, but  to establish which will be the main disciplinary  and thinking influences in the historiographical  work of this researcher. Preferably, the epistemological perspective of  Bermúdez is analyzed in which the positivist  methodology of his historiographical research  is discussed and compared to his narrative  technique, especially his published tales where  other possibilities are opened to understand this  author Ìs thought
Keywords: Historiography; Positivism; Nitrate History; Narrative Technique